Bioinspired Hierarchically Structured All‐Inorganic Nanocomposites with Significantly Improved Capacitive Performance - Yuan, Qibin; Yao, Fang‐Zhou; Cheng, Shao‐Dong; Wang, Linxi; Wang, Yifei; Mi, Shao‐Bo; Wang, Qing; Wang, Xiaohui; Wang, Hong (Advanced functional materials, 2020)
Lead‐free dielectric ceramics have been the spotlight in the search for environmentally benign materials for electrostatic energy storage because of the ever‐increasing environmental concerns. However, the inverse correlation between the polarization and dielectric breakdown strength is the major barrier hindering the provision of sufficient energy densities in lead‐free dielectric ceramics and practical applications thereof. Herein, a rational structure design inspired by nature is demonstrated as an effective strategy to overcome these challenges. Bioinspired raspberry‐like hierarchically structured all‐inorganic nanocomposites have been prepared by enclosing microsized BaTiO3‐Bi(Mg0.5Zr0.5)O3 (BT‐BMZ) relaxor ferroelectrics using core‐shell BT‐BMZ@SiO2 nanoparticles. The synergistic effects of the bioinspired hierarchical structure and insulating SiO2 nano‐coating result in significantly improved dielectric breakdown strength and sustained large polarization in the nanocomposites, as corroborated by experimental characterizations and theoretical simulations. As a result, an ultrahigh energy density of 3.41 J cm−3 and a high efficiency of 85.1%, together with outstanding thermal stability within a broad temperature range, have been simultaneously achieved in the hierarchically structured nanocomposites. This contribution provides a feasible and paradigmatic approach to develop high‐performance dielectrics for electrostatic energy storage applications using bioinspired structure design. A conceptual material paradigm of structure design strategy inspired by nature is developed to break the inverse correlation between polarization and breakdown strength inherently existing in dielectrics, and thus to boost their energy storage performance, as successfully validated by the bioinspired hierarchical structured all‐inorganic BaTiO3‐Bi(Mg0.5Zr0.5)O3‐based nanocomposites with a high energy density of 3.41 J cm−3, and efficiency of 85.1% simultaneously.